Mingantu Spectral Radioheliograph for Solar and Space Weather Studies - Yan, Yihua; Chen, Zhijun; Wang, Wei; Liu, Fei; Geng, Lihong; Chen, Linjie; Tan, Chengming; Chen, Xingyao; Su, Cang; Tan, Baolin (Frontiers in Astronomy and Space Sciences, 2021)
The Chinese Spectral Radioheliograph (CSRH) covering 400 MHz-15 GHz frequency range was constructed during 2009-2016 in Mingantu Observing Station, National Astronomical Observatories, Chinese Academy of Sciences at Zhengxiangbaiqi, Inner Mongolia of China. CSRH is renamed as {\it M}ingant{\it U} {\it S}p{\it E}ctral {\it R}adioheliograph (MUSER) after its accomplishment. Currently, MUSER consists of two arrays spreading over 3 spiral-shaped arms of $\sim$3 km maximum baseline in both east-west and north-south directions. MUSER array configuration is optimized to meet the needs of observing the full-disk Sun over ultrawide wavebands with high temporal, spatial and spectral resolution and a high dynamic range of images. MUSER-I covers 400 MHz-2.0 GHz with 40 4.5-m-diameter antennas and MUSER-II covers 2-15 GHz with 60 2-m-diameter antennas. MUSER-I can obtain solar full-disk radio images in 64 frequency channels with 25 ms cadence and 51.6$^{′′}$ to 10.3$^{′′}$ spatial resolution corresponding to the frequency range from 400 MHz to 2 GHz, whereas MUSER-II can obtain full-disk images in 520 channels with 206.25 ms cadence and 10.3$^{′′}$ to 1.3$^{′′}$ resolution from 2 to 15 GHz. Snapshot image quality with 25 dB dynamic range can be realized. The extension of MUSER to lower frequency band covering 30 MHz - 400 MHz with an array of 224 logarithm-periodic dipole antennas (LPDAs) has been approved and will be constructed during the next 4 years. MUSER has the following merits as a solar dedicated instrument: unique high temporal-spatial-spectral resolutions simultaneously over a wide frequency range; innovative high-performance ultrawide-band, dual-polarization feeds for wideband signal collection; advanced high data-rate, large-scale digital correlation receiver for multiple-frequency and fast snapshot observations; and applications of new technologies such as using optical fiber to realize remote antenna and wide-band analog signal transmission. MUSER opens a new window to measure the solar magnetic fields, trace the dynamic evolution of energetic electrons in radio frequencies, which will help us to better understand the origin of solar activities and the basic drivers of space weather.